2019
DOI: 10.21037/tau.2019.06.17
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cell only syndrome induced by a varicocele

Abstract: A case is reported which describes the severity of testicular histological damage that can be induced by a high-grade varicocele in a male with secondary infertility. A chart review of a patient's case was performed. A 34-year-old male with a three-and-a-half-year-old son who was conceived spontaneously with timed intercourse, with a grade three left varicocele, who's semen parameters progressed to non-obstructive azoospermia (NOA). He did not regain sperm in the ejaculate three or six months post left subingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…showed that there is a 10–50% chance of sperm-return in patients with NOA after varicocele repair. This study also revealed that a high-grade varicocele might cause the most severe form of NOA (i.e., Sertoli cell only syndrome) over time [ 48 ]. Therefore, the timing of varicocele repair could play a crucial role in couples seeking to have a biological child.…”
Section: Discussionmentioning
confidence: 99%
“…showed that there is a 10–50% chance of sperm-return in patients with NOA after varicocele repair. This study also revealed that a high-grade varicocele might cause the most severe form of NOA (i.e., Sertoli cell only syndrome) over time [ 48 ]. Therefore, the timing of varicocele repair could play a crucial role in couples seeking to have a biological child.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the patient is male with normal external genitalia, well-developed secondary sexual characteristics and azoospermia ( Hanmayyagari et al ., 2015 ). It is one of the most serious forms of non-obstructive azoospermia, and may be associated with other clinical manifestations in some cases ( Kavoussi et al ., 2019 ; Paduch et al ., 2019 ). However, the main complaint that makes the couple seek medical advice is the unsuccessful attempt at pregnancy ( Kim et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leydig’s interstitial cells are present and produce testosterone normally. It can be primary, characterized by a reduction in growth factors GDNF, FGF8 and BMP4 - that at low levels do not induce replication and the stimulus for the differentiation of spermatogenic stem cells into spermatogonia or, secondary, as Klinefelter’s Syndrome, exposure to toxins or chemicals, viruses, radiotherapy, trauma and varicocele ( Gat et al ., 2019 ; Behre et al ., 2015 ; Kavoussi et al ., 2019 ; Paduch et al ., 2019 ; Stouffs et al ., 2016 ; Nistal et al ., 1990 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations